An approach on place attachment, involvement and behavioural intentions in cross-border tourist regions - Sousa, Bruno (2014)
This study aims at gaining a deeper understanding of customer profiling and behaviour in cross-border tourism destinations. The study is developed under a niche marketing perspective. It is our view that niche marketing is not confined to the limits of national markets. Previous studies suggest that cross-border regions are an attractive notion, yet they require further theoretical and empirical research. There is still a gap in the understanding of destination management in cross-border regions and the customer profile and motivations. Overall this research attempts to produce a deeper understanding of the profile and behaviour of consumers in tourism settings, addressing the predisposition for the destination in specific contexts (cross-border tourism regions).